1991
DOI: 10.1007/bf00170698
|View full text |Cite
|
Sign up to set email alerts
|

The effect of wavelength on glial fibrillary acidic protein immunoreactivity in laser-induced lesions in rabbit retina

Abstract: Rabbit retinas were treated with low-intensity laser coagulation at five different wavelengths. Using an indirect immunocytochemical method, the retinas were stained for glial fibrillary acidic protein (GFAP) at 2, 4, 21 and 32 days after coagulation such that we could follow GFAP expression in the Müller cells during retinal repair. GFAP-positive staining was found in the end feet of the Müller cells at 2 days after laser coagulation. GFAP immunoreactivity was observed throughout the Müller cells, surrounding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…but can be induced t o do so by a variety of injury stimuli (Bignami and Dahl, 1979; Burns and Robles, 1990; Eisenfeld et al, 1984;Ekstrom et al, 1988; Erickson et al, 1987Erickson et al, , 1992; Humphrey et al, 1993; Okada et al, 1990; Roque and Caldwell, 1990; Sarthy and Fu, 1989; Scherer and Schnitzer, 1991; Tassignon et al, 1991). We have previously reported that there is a very widespread induction of GFAP-immunoreactivity in Muller cells following focal argon laser photocoagulation (Humphrey et al, 1993).…”
Section: Introductionmentioning
confidence: 92%
“…but can be induced t o do so by a variety of injury stimuli (Bignami and Dahl, 1979; Burns and Robles, 1990; Eisenfeld et al, 1984;Ekstrom et al, 1988; Erickson et al, 1987Erickson et al, , 1992; Humphrey et al, 1993; Okada et al, 1990; Roque and Caldwell, 1990; Sarthy and Fu, 1989; Scherer and Schnitzer, 1991; Tassignon et al, 1991). We have previously reported that there is a very widespread induction of GFAP-immunoreactivity in Muller cells following focal argon laser photocoagulation (Humphrey et al, 1993).…”
Section: Introductionmentioning
confidence: 92%
“…A discrepancy between the immunoblot and the immunohistochemi cal data could be foreseen since GFAP epi topes are sensitive to aldehyde fixation [2], The correlation found between retinal dam age and GFAP induction corroborates earlier Glial Response to Light-Induced Photoreceptor Damage observations reported by Burns and Robles [7], Tassignon ct al. [8] and Humphrey ct al. [9].…”
Section: Discussionmentioning
confidence: 99%
“…GFAP is the major compo nent of glial intermediate filaments found in astrocytes and has been generally accepted as an astrocyte-specific cell marker [1], In the retina of land vertebrates, GFAP is only present in the end-foot of Müller cells, if at all [2], However, Müller cells accumulate GFAP in response to retinopathy of prematurity [3], penetrating ocular injury [4], lensectomy-vitrectomy [5], light damage [6][7][8][9][10], aging [11], glaucoma [12], gliosis [13], experimental reti nal detachment [12,14], reduced ocular blood flow [15,16] and inherited retinal dystrophy [6,17], and elaborate an extensive network of glial filaments throughout their cytoplasm. This increase in intermediate filament is in herent in the reactive gliosis process and is thought to stabilise the new and enlarged glial processes which extend into the space left by the degenerating photoreceptors [14], Both focused laser irradiation of short du ration (milliseconds) [8,9] and prolonged ex posure (hours) to diffuse light of low energy [6,7,10] induce retinal lesions. In our labora tory, low intensity diffuse white fluorescent light (1,000 lx for 2 h) is used to induce retinal photoreceptor damage in albino rats.…”
Section: Introductionmentioning
confidence: 99%
“…All proceedings and animal treatment were in accordance with the guidelines and To asses the trauma imposed by the laser photocoagulation on the neuroretina, sections from all eyes were also labeled with an antibody raised against glial fibrillary acidic protein (GFAP, clone G-A-5, Boehringer Mannheim Scandinavia AB, Bromma, Sweden), which is expressed in activated Müller cells in response to retinal injury [2,17]. This antibody was used at a dilution of 1:4 and fluorescein isothiocyanate (FITC) was used as secondary antibody.…”
Section: Anaesthesia and Euthanasiamentioning
confidence: 99%